Knowledge about Blood Donation among the Clinical-year Medical Students of Khon Kaen University - Apipattarakul, Ruethairat; Chainaranon, Kannika; Boonyong, Thotsaporn; Maneesoi, Siwaree; Hemanak, Sutthasinee; Phosrisook, Korn; Bubphan, Tunlaphat; Thanabura, Soraj; Ratanasiri, Amornrat; Luvira, Varisara; Paupairoj, Chintana (Srinagarind Medical Journal, 2013)
Background and objectives: The Clinical-year medical students who are working closely with the patients should have a working knowledge of blood donation. This study aims to determine the proportion of the clinical - year medical students on their general and clinical knowledge of blood donation and to determine the relationship between general and clinical knowledge of blood donation . Methods: This was a descriptive study, setting in the Faculty of Medicine , Khon Kaen University, Thailand. The study population was 113 clinical-year medical students, randomly sampling from the total number of 441and self-administered questionnaire were used. Results were presented as descriptive statistics and inferential statistics included Pearson Chi-Square, Linear by Linear Association and Kruskal-Wallis test. Results: Response rate was 100%. The survey showed, proportion of good knowledge on general knowledge about blood donation was 74.3% (95%CI: 65.1, 81.9). There was 7.1% of sample had good level, 76.1 % had fair level and 16.8 % had poor level of knowledge on clinical knowledge about blood donation. There was 54% of sample blood donation. This study found statistically significant between knowledge on general blood donation (p <0.05) while there was no statistical significant between clinical knowledge about blood donation (p >0.05) Conclusions: Most of the clinical - year medical students known general knowledge and fair level in clinical knowledge of blood donation. Level of general knowledge of blood donation was significantly associated with donating, but no statistical significant between clinical knowledge about blood donation. Keyword: knowledge, blood donation, medical students